2018
DOI: 10.1111/mmi.14064
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of the yellow xanthomonadin pigments involves an ATP‐dependent 3‐hydroxybenzoic acid: acyl carrier protein ligase and an unusual type II polyketide synthase pathway

Abstract: Xanthomonadins are yellow pigments that are produced by the phytopathogen Xanthomonas campestris pv. campestris (Xcc). A pig cluster is responsible for xanthomonadin biosynthesis. Previously, Xcc4014 of the cluster was characterized as a bifunctional chorismatase that produces 3-hydroxybenzoic acid (3-HBA) and 4-HBA. In this study, genetic analysis identified 11 genes within the pig cluster to be essential for xanthomonadin biosynthesis. Biochemical and bioinformatics analysis suggest that xanthomonadins are s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…The promising anticancer activities and the obscure biosynthetic origin of unantimycins prompted us to investigate further the biosynthetic pathway. Documentedly, 3-HBA generated by chorismatase from chorismate can be recruited as starting precursor in the biosynthesis of polyketides BC325, cuevaene, and xanthomonadin (14)(15)(16)(17) or as donor group in the late modification stage of terpenoid brasilicardin biosynthesis (18) (Fig. 2).…”
Section: Introductionmentioning
confidence: 99%
“…The promising anticancer activities and the obscure biosynthetic origin of unantimycins prompted us to investigate further the biosynthetic pathway. Documentedly, 3-HBA generated by chorismatase from chorismate can be recruited as starting precursor in the biosynthesis of polyketides BC325, cuevaene, and xanthomonadin (14)(15)(16)(17) or as donor group in the late modification stage of terpenoid brasilicardin biosynthesis (18) (Fig. 2).…”
Section: Introductionmentioning
confidence: 99%
“…In our study, Xcc fabG3 deletion abolished xanthomonadin production, which indicated that FabG3 plays a vital role in xanthomonadin synthesis. Cao et al (2018) identified 11 genes (named xanA2 to xanM, respectively) within the pig cluster as being essential for xanthomonadin synthesis, in which the ketoreductase-coding gene xanH corresponds to fabG3 in this study.…”
Section: Discussionmentioning
confidence: 76%
“…Xcc utilizes 3-hydroxybenzoic acid (3-HBA), a diffusible factor with regulatory function, as the precursor for xanthomonadin synthesis, and 3-HBA is synthesized by a unique bifunctional chorismatase XanB2 (He et al, 2011;Wang et al, 2015;Zhou et al, 2013a, b). Recently, Cao et al (2018) reported only 11 genes are responsible for xanthomonadin biosynthesis, and xanC encodes an acyl carrier protein (ACP) while xanA2 encodes the 3-HBA:ACP ligase to initiate xanthomonadin biosynthesis. However, further studies are required to define the detailed mechanisms of xanthomonadin synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…3A ). pchAB is responsible for the production of SA, a precursor for pyochelin, in Pseudomonas aeruginosa ( 37 ). When the Δ rpfC and Δ rpfC :: pchAB strains were grown in XYS medium, SA levels in Δ rpfC :: pchAB cultures were 55.1 μM at 12 hpi, 95.5 μM at 24 hpi, and 124.6 μM at 36 hpi, while SA was not detected in Δ rpfC cultures ( Fig.…”
Section: Resultsmentioning
confidence: 99%